ANALISIS PERBANDINGAN KINERJA KEUANGAN SEKTOR PERBANKAN DENGAN METODE CAMEL DI INDONESIA (STUDI KOMPARATIF: BPD, BANK BUMN, BANK SWASTA NASIONAL, DAN BANK ASING) - Pangihutan Siallagan; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2016)
This study aimed to compare the financial performance of the banking sector between the regional development banks, government-owned banks, national private banks and foreign banks were assessed with the CAMEL method on the timeframe 2013 – 2015. The CAMEL method is performance assessment reviewed aspects of Capital, Asset Quality, Management, Earnings, Liquidity. The variables in this study is the ratio-financial ratio used in the assessment of the financial performance of the bank. Ratio-the ratio used is the Capital Adequacy Ratio (CAR), the Non Performing Loan (NPL), Expenditure to Income Ratio, Return on Assets (ROA), Return on Equity (ROE), and Loan to Deposit Ratio (LDR).This study uses secondary data i.e. financial statements and annual reports published by the bank. Information of financial ratio obtained from the financial reports and the annual report of the bank. The selection of the sample in this study using the purposive sampling method. Technique of data analysis in this study uses descriptive statistics and Kruskal Wallis tests to find out if there is a difference based on the bank's financial performance motode CAMEL on any type of bank.The results showed that foreign banks have the best performance in terms of aspect capital and asset quality, the govenrment-owned bank have the best performance in terms of earnings and management aspects, and national private banks have the best performance in terms of liquidity aspects. Kruskal Wallis test based on it can be concluded that there is a difference between regional development bank financial performance, the govenrment-owned bank, national private banks and foreign banks on a CAR, NPL, ratio of Expenditure to Income Ratio, ROA, ROE, and LDR.